FRI0084 Structural progressors in rheumatoid arthritis identified by serology – identification of the patients in most need of intensive treatment. (23rd January 2014) - Karsdal, M. A.; Siebuhr, A. S.; Leeming, D. J.; Byrjalsen, I.; Christiansen, C.; Platt, A.; Bay-Jensen, A.-C.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease with highly elevated connective tissue turnover. It is important to identify patients with rapid progression, as these are in most need of immediate treatment to preserve tissue integrity. Matrix Metalloproteinase (MMP) mediated connective tissue destruction is central in RA and results in the release of protein fragments into circulation. One of these protein fingerprints is C1M; an MMP-mediated fragment of type I collagen. We developed an ELISA detecting the circulating C1M fragment specifically; thus, the assays do not recognize intact collagen or other collagens and is not a product of other enzymes, exclusively MMPs. Objectives: The aim was to investigate whether: 1) serum C1M baseline levels were correlated with structural status and progression in the placebo group; and 2) C1M was a potential surrogate marker of efficacy. Methods: The LITHE biomarker study (n=586, ROCHE WA 17823) was a 2-year phase III, double-blind, placebo (PBO)-controlled, parallel group study of Tocilizumab (TCZ; 4 mg/kg and 8 mg/kg, every 4 weeks) in patients with moderate to severely active RA on stable doses of Methotrexate (MTX; 10-25mg/week). C1M was tested in serum samples from baseline and week 2, 4, 16, 24 and 52. Spearman's correlation was analyzed between baseline serum C1M (log transformed) levels and VAS pain, DAS, JSN and mTSS. The associations between baseline serum C1M and change in JSN and mTSS were investigated in the PBO group by regressions analysis, including CRP, age, BMI, disease duration and baseline JSN/mTSS. Changes in serum C1M levels were studied as a function of time and treatment. Results: Baseline serum C1M was significantly correlated with change in JSN at week 24 (r=0.38 p<0.0001) and at week 52 (r=0.63, p<0.0001). At baseline, levels of C1M were significantly correlated to VAS pain (rho=0.22, p=0.0023), CRP (rho=0.85, p<0.0001) and DAS (0.31, p<0.0001). Baseline levels were not correlated to baseline mTSS (rho=0.14) or JSN (rho=0.12). Baseline serum C1M was correlated with changes in mTSS at 24 (r=0.21 p<0.012) and 52 week (r=0.58, p<0.0001). Serum C1M was dose-dependently reduced by TCZ8+MTX (p<0.0001) and TCZ4+MTX (p<0.05) as compared to PBO+MTX (figure ). Image/graph: Conclusions: MMP-mediated tissue degradation is imperative in joint destruction, as those patients with the highest levels of C1M were significantly more likely to progress in JSN and mTSS compared to those with a low level. C1M may assist in identifying those patients that are rapid progressors. Interestingly, TCZ dose-dependently inhibited C1M level already after 2 weeks, suggesting swift onset of joint protection. C1M may both be a surrogate marker of structural efficacy and enable prognostic identification of those patients that are in most need of treatment. Disclosure of Interest: M. Karsdal Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, A. S. Siebuhr Employee of: Nordic Bioscience, D. Leeming Employee of: Nordic Bioscience, I. Byrjalsen Employee of: Nordic Bioscience, C. Christiansen Shareholder of: Nordic Bioscience, A. Platt: None Declared, A.-C. Bay-Jensen Employee of: Nordic Bioscience